2021
DOI: 10.3389/ffgc.2021.664763
|View full text |Cite
|
Sign up to set email alerts
|

Herbaria Reveal Herbivory and Pathogen Increases and Shifts in Senescence for Northeastern United States Maples Over 150 Years

Abstract: Recent studies suggest climate-related delays in the timing of leaf coloration and abscission in maple trees but lack baseline data prior to the late 20th century. To better understand how autumn foliar phenology and late-season damage risks have changed for this genus over the past century, we evaluated 2,972 digitized herbaria specimens of red and sugar maple collected between 1826 and 2016 for the presence of leaves, autumn leaf coloration, and pathogen or herbivore damage. We found that the onset (first ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…We also found that species phenology occurring later in the monitoring season are advancing more rapidly, particularly within the monitored animals (Figure 1B). While our phenological monitoring does not span the full year and focuses on spring and summer phenophases, our finding underscores the importance of monitoring species throughout the year and suggests that late summer and fall phenophases may be particularly important in understanding the impacts of climate change on ecosystems and species interactions (31)(32)(33)(34). Finally, our results underscore the importance of using appropriate modeling approaches, as linear estimation methods yield lower shifts relative to circular estimation methods, particularly for species that have seen dramatic shifts over the study period (Figure 1A).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We also found that species phenology occurring later in the monitoring season are advancing more rapidly, particularly within the monitored animals (Figure 1B). While our phenological monitoring does not span the full year and focuses on spring and summer phenophases, our finding underscores the importance of monitoring species throughout the year and suggests that late summer and fall phenophases may be particularly important in understanding the impacts of climate change on ecosystems and species interactions (31)(32)(33)(34). Finally, our results underscore the importance of using appropriate modeling approaches, as linear estimation methods yield lower shifts relative to circular estimation methods, particularly for species that have seen dramatic shifts over the study period (Figure 1A).…”
Section: Discussionmentioning
confidence: 95%
“…This is because phenological analyses are traditionally conducted using only linear analysis models, in regions with a single growing season, and tend to focus on summer or spring phenophases that do not cross the boundary of the yearly date cycle (28)(29)(30). However, it is increasingly recognized that the widely observed changes in spring and summer are also seen in fall and winter (15,(31)(32)(33)(34). Circular statistics offer a potential solution to concerns with modeling cyclical phenomena with phenological datasets that cover much of the yearly cycle, by expressing dates as angular directions distributed across a circumference (35,36).…”
Section: Introductionmentioning
confidence: 99%
“…Fitak & Johnsen, 2017; Ożarowska et al., 2013); ecophysiology (e.g. Garretson & Forkner, 2021; Pabon‐Moreno et al., 2020); and reproduction (e.g. Morellato et al., 2010; Staggemeier et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the granularity of minimum convex polygons is limited and cannot provide insight into internal barriers to species range (e.g., mountain ranges or bodies of water that may limit dispersal) [28,29]. Lastly, there has been a significant increase in the number of occurrence records since 2016 due in large part to the increased digitization of museum collections and the availability of citizen science data [30][31][32]. These emergent resources have not yet been brought to bear on estimates of the house mouse species range.…”
Section: Introductionmentioning
confidence: 99%